'I have two homelands': constructing and managing Iranian Jewish and Persian Israeli identities. Issue 2 (2nd April 2016) - Jaspal, Rusi
Abstract: Israel and the Islamic Republic of Iran have had a problematic relationship for the last four decades. Despite their tense relations, Israel is home to thousands of Persians and Iran has the second largest Jewish population in the Middle East. There are social, political and psychological obstacles to dual identification. Using qualitative thematic analysis and Identity Process Theory, this article examines the construction and management of Persian/Iranian and Jewish/Israeli identities among these groups. The following themes are discussed: (1) the challenges and maintenance of dual identification, (2) breaking down boundaries between identities, and (3) Persian-Iranian or Jewish-Israeli? Establishing coherence in identity. Results suggest that, while the social and political institutions in Iran and Israel construct barriers to dual identification, individuals deploy creative strategies for constructing an ethnic identity that acknowledges both components of their heritage. The implications for self-identity are discussed.